Effects of Probiotics at the Interface of Metabolism and Immunity to Prevent Colorectal Cancer-Associated Gut Inflammation: A Systematic Network and Meta-Analysis With Molecular Docking Studies - Patra, Sinjini; Sahu, Nilanjan; Saxena, Shivam; Pradhan, Biswaranjan; Nayak, Saroj Kumar; Roychowdhury, Anasuya (Frontiers in Microbiology, 2022)
BACKGROUND: Dysbiosis or imbalance in the gut microbial composition triggers chronic inflammation and promotes colorectal cancer (CRC). Modulation of gut microbiome by administration of probiotics has been recognized as a promising strategy to reduce carcinogenic inflammation. However, the mechanism remains unclear. METHODS: Here, we present a systematic network, meta-analysis, and molecular docking studies to determine the plausible mechanisms for probiotic intervention in diminishing CRC-related inflammations. RESULTS: We select 77 clinical, pre-clinical, in-vitro, and in-vivo articles (PRISMA guidelines), identify 36 probiotics and 135 training genes connected to CRC patients with probiotic application. The meta-analysis rationalizes the probiotic application in the prevention and treatment of CRC. An association network is generated with 540 nodes and 1423 edges. MCODE cluster analysis identifies 43 densely interconnected modules from the network. Gene Ontology (GO) and pathways enrichment analysis of the top scoring and functionally significant modules reveal stress-induced metabolic pathways (JNK, MAPK), immunomodulatory pathways, intrinsic apoptotic pathway, and autophagy as contributors for CRC where probiotics could offer major benefits. Based on the enrichment analyses, 23 CRC-associated proteins and 7 probiotic-derived bacteriocins are selected for molecular docking studies. Results indicate key CRC-associated proteins (e.g., COX-2, CASP9, PI3K, IL18R, etc.) significantly interact with the probiotic-derived bacteriocins (e.g., plantaricin JLA-9, lactococcin A, lactococcin Mmfii, etc.). Finally, a model is proposed for probiotic intervention to reduce CRC-associated inflammation. CONCLUSION: In summary, probiotics and/or probiotic-derived bacteriocins could directly interact with CRC-promoting COX2, they could modulate inflammatory NLRP3, and NFkB pathways to reduce CRC-associated inflammation and finally, probiotics also could activate autophagy and apoptosis by regulating PI3K/AKT and caspase pathways in CRC. Thus, the potential mechanisms of probiotic-mediated CRC prevention include multiple signalling cascades, yet, pathways related to metabolism and immunity are the crucial ones.